Progesterone dose during synchronization treatment alters luteinizing hormone receptor and steroidogenic enzyme mRNA abundances in granulosa cells of Nellore heifers - Dias, H. P. [UNESP]; Poole, R. K.; Albuquerque, J. P. [UNESP]; Santos, P. H. dos [UNESP]; Castilho, A. C. S.; Pohler, K. G.; Vasconcelos, J. L. M. [UNESP] (Elsevier B.V., 2021)
The objective was to investigate effects of progesterone (P-4) dose on abundance of luteinizing hormone receptor (LHCGR), aromatase (CYP19A1), 3 beta-hydroxysteroid dehydrogenase (HSD3B1), and other steroidogenic mRNA transcripts in granulosa cells from dominant follicles. Nellore heifers were assigned to one of six groups: new, first-use controlled internal drug release device (CIDR1) inserted for 5 days (Large-P-4-dose-D5; n = 7) or 6 days (Large-P-4-dose-D6; n = 8), prostaglandin (PG)F-2 alpha administered on DO and 1 previously-used CIDR (CIDR3) inserted for 5 days (Small-P-4-dose-D5; n = 8) or 6 days (Small-P-4-dose-D6; n = 8), CIDR1 inserted on DO and removed plus PGF(2 alpha) on D5 (Large-P-4-dose-pmestrus (PE); n = 7), and CIDR3 and PGF(2 alpha) on DO and 1, CIDR3 removed plus PGF(2 alpha) on D5 (Small-P-4-dose-PE; n = 7). Duration of P-4 treatment (D5 compared to D6) affected abundances of CYP19A1 mRNA transcripts, with there being greater abundances on D6 than D5 (P <= 0.05). Heifers treated with the large dose of P-4 had a smaller dominant follicle, less serum and intra-follicular estradiol (E-2) concentrations (P <= 0.05) and lesser LHCGR, CYP19A1, and HSD3B1 transcript abundances (P <= 0.05). Heifers treated to induce PE had a larger follicle diameter (P = 0.09), greater intra-follicular E-2 concentrations and larger abundances of CYP19A1 mRNA transcript (P <= 0.05) than heifers of the D6 group. Overall, treatment with larger doses of P-4 resulted in lesser abundances of LHCGR, HSD3B1, and CYP19A1 mRNA transcripts; thus, potentially leading to development of smaller dominant follicles and lesser E-2 concentrations.
Keywords: LH receptor; Progesterone; Granulosa cell; Nellore heifers